¿DIGO LO QUE SIENTO Y SIENTO LO QUE DIGO? UNA APROXIMACIÓN TRANSCULTURAL AL USO DE LOS EMOTICONOS Y EMOJIS EN LOS MENSAJES EN CMC - Dra. Lifen CHENG (Fonseca, Journal of Communication, 2023)
The use of emoticons and emojis among online messaging users has achieved a globalized level. This article aims at examining how certain emojis and emoticons are chosen by message senders to regular the intensity of emotions in their messages. Or, by means of using them, message senders wish to blur textual rigidity and show interaction empathy during the communication process. This study analyzes the use of these symbols and graphic elements in message exchange through CMC and SNS, where users from different culture background convey their feeling